Virus elimination in potato through meristem culture followed by thermotherapy - Ali, MA; Nasiruddin, KM; Haque, MS; Faisal, SM (SAARC Journal of Agriculture, 2014)
Virus elimination in potato through meristem culture followed by thermotherapy and virus indexing was studied. Three levels of thermotherapy, viz. 27±1°C (control), 30±1°C and 35±1°C, sixteen combinations of BAP (Benzyl Amino Purine) plus GA3 (gibberellic Acid) concentrations viz. 0.0+0.0 (control), 0.0+0.2, 0.0+0.4, 0.0+0.6, 1.5+0.0, 1.5+0.2, 1.5+0.4, 1.5+0.6, 3.0+0.0, 3.0+0.2, 3.0+0.4, 3.0+0.6 , 4.5+0.0, 4.5+ 0.2, 4.5+0.4 and 4.5+0.6 were used in this study in three potato varieties viz. Diamant, Heera and Lalpakri. Among the thermo therapies, 27±1°C showed the highest (24.55) survival response followed by 30±1°C, 35±1°C, respectively. The poorest (20.47) survival response of meristem derived plantlets was noticed in 35±1°C which gave the highest percentage (43.79) of virus free plantlets followed by 30±1°C. The best (25.85%) survival response was found in Lalpakri and the lowest (19.08%) survivality was recorded in Diamant. The highest (33.27) percentage of PVY (Potato Virus Y) free plantlets was observed in Heera. The combined treatment 3.0 mg L-1 BAP and 0.2 mg L-1 GA3 showed the highest (63.39) percentage of virus free plantlet production followed by 4.5 mg L-1 BAP and 0.2 mg L-1 GA3 DOI: http://dx.doi.org/10.3329/sja.v11i1.18376 SAARC J. Agri., 11(1): 71-80 (2013)